2017
DOI: 10.1007/s00224-017-9763-z
|View full text |Cite
|
Sign up to set email alerts
|

The Word Problem for Omega-Terms over the Trotter-Weil Hierarchy

Abstract: For two given ω-terms α and β, the word problem for ω-terms over a variety V asks whether α = β in all monoids in V. We show that the word problem for ω-terms over each level of the Trotter-Weil Hierarchy is decidable. More precisely, for every fixed variety in the Trotter-Weil Hierarchy, our approach yields an algorithm in nondeterministic logarithmic space (NL). In addition, we provide deterministic polynomial time algorithms which are more efficient than straightforward translations of the NL-algorithms. As… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…For instance, in [60,18] faithful representations of finitely generated free profinite semigroups over A were obtained. There is a common trend in these faithful representations of free profinite semigroups over A, R, or DA, and also in the partial faithful representations obtained in [68,72] for many other pseudovarieties: it is the fact they consist in viewing pseudowords as linearly ordered sets whose elements are labeled with letters, generalizing the fact that words are nothing else than such sets with a finite cardinal.…”
Section: Relatively Free Profinite Semigroupsmentioning
confidence: 99%
“…For instance, in [60,18] faithful representations of finitely generated free profinite semigroups over A were obtained. There is a common trend in these faithful representations of free profinite semigroups over A, R, or DA, and also in the partial faithful representations obtained in [68,72] for many other pseudovarieties: it is the fact they consist in viewing pseudowords as linearly ordered sets whose elements are labeled with letters, generalizing the fact that words are nothing else than such sets with a finite cardinal.…”
Section: Relatively Free Profinite Semigroupsmentioning
confidence: 99%
“…Several other authors have shown interest in better understanding DS [23,24,25]. Furthermore, the results found in the literature suggest that the investigation of subpseudovarieties of DS may lead to a better understanding of DS itself [26,27,17], and thus, DRH is an interesting instance.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, one of the pseudovarieties shown to be of great relevance is R, which consists of all finite semigroups whose regular R-classes are trivial. It appears naturally in different contexts (see, for instance, [14,15,16,17]), and has been the focus of many works (other examples are present in [18,19,20,21]). In turn, a natural generalization of R is found in the pseudovarieties of the form DRH for a pseudovariety of groups H. This class contains all finite semigroups whose regular R-classes are groups from H. Observe that, when H is the trivial pseudovariety, the pseudovariety DRH is precisely R.…”
Section: Introductionmentioning
confidence: 99%
“…Among pseudovarieties that have deserved a lot of attention, for their connections with formal language theory or for their inherent algebraic interest, is the pseudovariety R of all finite R-trivial semigroups, that is finite semigroups in which every principal right ideal admits only one element as a generator. Its word problem for the signature consisting of multiplication and the ω-power (which, in a finite semigroup, gives the idempotent power of the base) has a particularly nice solution [12] (see also [17]). Moreover, R has very strong tameness properties [7] with respect to this signature.…”
Section: Introductionmentioning
confidence: 99%